Chemical composition and anti-inflamatory, anti-nociceptive and antipyretic activity of rhizome essential oil of Globba sessiliflora Sims. collected from Garhwal region of Uttarakhand - Ravendra Kumar; Prakash Om; Pant Anil K; Kumar Mahesh; Isidorov Valary A; Szczepaniak Lech (Islamic Azad University, Shahrekord Branch, 2017)
Background & Aim: Family Zingiberaceae is worldwide in distribution. Plants of the zingiberaceae family are used in traditional herbal folk medicine besides their uses in spices, cosmetic, ornamental, food preservatives etc. In Uttarakhand the herbs grow from sub-tropical to temperate region. Globba sessiliflora Simsrhizomes were collected at maturity stage in November from Garhwal region of Uttarakhand, India. In present communication the medicinal use of various zingiberaceous herb provoked us to study the chemical diversity and pharmacological activity determination of this important traditional herb. Experimental: The essential oil was extracted using hydrodistillation method and analyzed by GC-MS. Anti-inflamatory, anti-nociceptive and antipyretic activities of essential oil were experimently determined using mice model. Results: The major compounds identified were β-eudesmol (27.6%), (E)-β-caryophyllene (24.3%), α-humulene (3.0%), (6E)-nerolidol (4.1%), caryophyllene oxide (9.7%), γ-eudesmol (6.4%) and τ-muurolol (8.3%) besides other minor constituents. Essential oil of G. sessiliflora rhizome showed good anti-inflamatory, anti-nociceptive and antipyretic activities at the dose level of 100 mg/kg body weight. The oral administration of the essential oil exhibited no toxicity at 400, 600 and 800 mg/kg b.wt. concentration. Ibuprofen, indomthacin and paracetamol were used as standard drugs for comparison. Recommended applications/industries: G. sessiliflora essential oil can be used as herbal remedy for its nontoxicityanti-inflamatory, anti-nociceptive and antipyretic activities.